Market Orientation and Export Performance under ASEAN–India Free Trade Agreement: The Case of India's Rubber and Rubber Products. Issue 2 (September 2019) - Joseph, Joby; Hari, K. S.
Abstract: The countries involved in the ASEAN–India Free Trade Agreement (AIFTA) are major producers/exporters of tropical commodities including natural rubber (NR). India is the sixth largest producer and second largest consumer of NR in the world. The country is also a major importer of NR and exporter of rubber products. The import of NR worth US 785.44 million and export earnings of rubber products worth US 244.17 million from ASEAN region during the year 2017–18 indicated the importance of AIFTA in the rubber sector of India. Therefore, an in-depth analysis on the pattern and specialisation of rubber and rubber products exported from India is done using trade indicators such as revealed comparative advantage, regional orientation, intra-industry trade and Galtonian regression. The results indicate no considerable change after the establishment of AIFTA in the pattern and specialisation in exports of rubber and rubber products from India to ASEAN.